Clinical Feature of Intrahepatic B-Lymphocytes in Chronic Hepatitis B - Ashraf Mohamadkhani; Elnaz Naderi; Masoud Sotoudeh; Aezam Katoonizadeh; Ghodratollah Montazeri; Hossein Poustchi (International Journal of Inflammation)
Humoral immunity constitutes major defense mechanism against viral infections. However, the association of hepatic injury and B-cells population in chronic hepatitis B virus (HBV) carriers has not been studied well. In this study, fifty seven hepatitis B surface antigen (HBsAg) positive and HBeAg negative patients were studied to determine the expression of CD20, a cell surface marker expressed on B-cells, in liver biopsy sections using immunohistochemistry. The patients’ clinical data at the time of liver biopsy were acquired from their medical records. There was a significant association between log HBV DNA and both ALT (r=0.36, P=0.006) and histologic activity index (HAI) total score (r=0.3, P=0.02), respectively. The CD20 was expressed in all 57 liver biopsy samples with a submembranous and membranous staining pattern and its expression was significantly associated with HAI total score (r=0.32, P=0.01) and stage of fibrosis (r=0.31, P=0.02). The susceptible B lymphocytes to hepatitis B virus might be implicated in the development of immune mediated inflammation of HBV-induced hepatic injury. The present data also support that the liver is potentially one of the secondary lymphoid organs.